Comparing Student Performance in Individual and Collaborative Problem-Based Learning in The Basic Power System Course - Adrianti; Muhammad Nasir (Andalas Journal of Electrical and Electronic Engineering Technology, 2026)
Collaborative learning is associated with higher achievement, improved social connections, enhanced communication skills, and increased self-esteem. However, challenges such as a lack of collaboration skills, unequal participation, and free riding can hinder its effectiveness. It emphasizes the need for students to develop individual learning skills—such as analysis, synthesis, and reflection—before engaging in collaborative learning to ensure success. The paper aims to analyze and compare students' learning performance in a Basic Power System course over two consecutive years, in which the first year employed collaborative learning strategies and the second year used individual learning strategies, involving fourth-semester students in an Electrical Engineering Bachelor's program. The comparison of student marks between the 2022/2023 and 2023/2024 academic years indicates that individual assignments resulted in better performance, surpassing group assignments by an average of 23.7%. Exam results corroborate these findings: the 2023/2024 cohort surpassed the target scores, while the previous year's results fell significantly short. Despite this improvement, the exam results for both years were unsatisfactory, suggesting a need for more effective learning strategies, particularly those that boost students' self-efficacy in mastering course materials.